2010
DOI: 10.1259/bjr/88793106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between blinded and partially blinded detection of gastric cancer with multidetector CT using surgery and endoscopic submucosal dissection as reference standards

Abstract: ABSTRACT. The aim of this study is to compare blinded with partially blinded detection of gastric cancer with multidetector (MD) CT by using surgery and endoscopic submucosal dissection (ESD) as reference standards. 44 patients with gastric cancer underwent MDCT with air as an oral contrast agent. Surgery was performed on 37 patients, ESD on six and surgery after ESD on one. To provide comparison cases of blinded evaluation, 38 MDCT examinations were added for cases where no focal gastric lesion was seen on en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Similar to this study, many other studies did not include patients without gastric cancer as the control group [3, 12, 15, 20]. Kim et al [21] and Park et al [22] used partially and completely blind methods in their gastric cancer studies and showed no difference in the two methods. Hence, the present study was not affected by the lack of a negative contrast group.…”
Section: Discussionsupporting
confidence: 58%
“…Similar to this study, many other studies did not include patients without gastric cancer as the control group [3, 12, 15, 20]. Kim et al [21] and Park et al [22] used partially and completely blind methods in their gastric cancer studies and showed no difference in the two methods. Hence, the present study was not affected by the lack of a negative contrast group.…”
Section: Discussionsupporting
confidence: 58%
“…According to previous studies in which an MDCT scanner was used, the detection rate of gastric cancer on 2D axial CT and MPR was between 62% and 98%. However, the detection rate of EGC on 2D axial CT and MPR is generally low, i.e., between 41.2% and 71% [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…previous reports, the detection rate of gastric cancer on 2D axial CT varies between 20% and 91% [3][4][5][6][7].…”
mentioning
confidence: 87%